Absent Inclusion Polices: Problems Facing Homeless Transgender Youth. (2nd November 2018) - Sellers, Mitchell Dylan
Abstract : Transgender individuals make up a disproportionately high percentage of homeless youth. This is due to conflict with their family, harassment in schools, or negative interactions with child services. In addition to the typical needs of homeless youth, questions arise regarding housing, changing the youth's name and gender, and access to healthcare. Analysis examines what protections and services subnational governments provide to homeless transgender youth as of 2016. The findings indicate that state and local governments provide most nondiscrimination protections for these youths, with local government outreach programs specializing services for homeless and transgender populations. It is more common for states not to have nondiscrimination policies for the lesbian; gay; bisexual; and transgender community. However, several states have extensive protections for transgender individuals to remove discriminatory practices that contribute to homelessness, such as in housing or foster care. Findings also show that more than 350 municipalities have policies that explicitly protect the transgender community. These policies typically ban discrimination in policy areas, like education and employment, but some local governments went beyond these basic protections to serve vulnerable populations better. Although few governments formally create policies to work with homeless and transgender populations, more than a quarter of governments offer testing and treatment for HIV.